2008
DOI: 10.1080/13504860701269285
|View full text |Cite
|
Sign up to set email alerts
|

Market Influence of Portfolio Optimizers

Abstract: We study the feedback effects induced by portfolio optimizers on the underlying asset prices.Through their interaction with reference traders, who trade based on some aggregate incomes process, they are assumed to move asset prices away from the standard log-normal model. With market clearing as our main constraint, we solve analytically for the approximate dynamics of the asset price assuming that the wealth of the portfolio optimizers is small relative to the total market capitalization of the stock. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…We have checked that (34) has excellent agreement with the order ǫ asymptotic expansion derived by Nayak and Papanicolaou [28] in the small feedback regime.…”
Section: B Application To Equity Marketmentioning
confidence: 65%
See 3 more Smart Citations
“…We have checked that (34) has excellent agreement with the order ǫ asymptotic expansion derived by Nayak and Papanicolaou [28] in the small feedback regime.…”
Section: B Application To Equity Marketmentioning
confidence: 65%
“…In Section 4 we present the numerical solutions to the first couple of stages and quantify the induced correlation between the equity and commodity markets. In Appendix B we return to the feedback model of Nayak and Papanicolaou [28] and present an explicit solution to the first stage in the feedback sequence which greatly facilitates the model analysis. Appendix C provides a tractable but less realistic model with exponential utility, where the full fixed point problem can be reduced to solution of a system of ordinary integro-differential equations.…”
Section: Organizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Their paper showed that hedging strategies increase the volatility of the underlying asset. Nayak and Papanicolaou [11,12] extended the methods developed in that paper to the situation where portfolio optimizers cause deviation from a simple log-normal model.…”
Section: Introductionmentioning
confidence: 99%